Hubungan keterampilan bertanya guru dengan hasil belajar kognitif IPAS materi cerita tentang daerahku kelas IV SD - Indah Permatasari; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2025)
Thoughtful questioning by teachers is essential for fostering students' critical thinking skills and actively involving them in the learning process. This study aims to determine the relationship between teacher questioning skills and cognitive learning outcomes in IPAS topic